SLURP-1 Controls Growth and Migration of Lung Adenocarcinoma Cells, Forming a Complex With α7-nAChR and PDGFR/EGFR Heterodimer - Bychkov, Maxim L.; Shulepko, Mikhail A.; Shlepova, Olga V.; Kulbatskii, Dmitrii S.; Chulina, Irina A.; Paramonov, Alexander S.; Baidakova, Ludmila K.; Azev, Viatcheslav N.; Koshelev, Sergey G.; Kirpichnikov, Mikhail P.; Shenkarev, Zakhar O.; Lyukmanova, Ekaterina N. (Frontiers in Cell and Developmental Biology, 2021)
SLURP-1 is a secreted Ly6/uPAR protein that negatively modulates the nicotinic acetylcholine receptor of α7 type (α7-nAChR), participating in control of cancer cell growth. Previously we showed, that a recombinant analogue of human SLURP-1 (rSLURP-1) diminishes the lung adenocarcinoma A549 cell proliferation and abolishes the nicotine-induced growth stimulation. Here, using multiplex immunoassay, we demonstrated a decrease in PTEN and mTOR kinase phosphorylation in A549 cells upon the rSLURP-1 treatment pointing on down-regulation of the PI3K/AKT/mTOR signaling pathway. Decreased phosphorylation of the platelet-derived growth factor receptor type β (PDGFRβ) and arrest of the A549 cell cycle in the S and G2/M phases without apoptosis induction was also observed. Using a scratch migration assay, inhibition of A549 cell migration under the rSLURP-1 treatment was found. Affinity extraction demonstrated that rSLURP-1 in A549 cells forms a complex not only with α7-nAChR, but also with PDGFRα and epidermal growth factor receptor (EGFR), which are known to be involved in regulation of cancer cell growth and migration and are able to form a heterodimer. Knock-down of the genes encoding α7-nAChR, PDGFRα, and EGFR confirmed the involvement of these receptors in the anti-migration effect of SLURP-1. Thus, SLURP-1 can target the α7-nAChR complexes with PDGFRα and EGFR in the membrane of epithelial cells. Using chimeric proteins with grafted SLURP-1 loops we demonstrated that loop I is the principal active site responsible for the SLURP-1 interaction with α7-nAChR and its antiproliferative effect. Synthetic peptide mimicking the loop I cyclized by a disulfide bond inhibited ACh-evoked current at α7-nAChR, as well as A549 cell proliferation and migration. This synthetic peptide represents a promising prototype of new antitumor drug with the properties close to that of the native SLURP-1 protein.